Study of Abdominal Injury: An Analysis of 50 Cases - Siddique, MAB; Rahman, MK; Hannan, ABMA (TAJ: Journal of Teachers Association, 2009)
Abdominal injury is an important aspect of trauma because of difficulty in diagnosis and its lethal potential if not properly treated. Fifty cases of abdominal injury admitted in the surgical wards of Rajshahi Medical College Hospital over 2 years have been studied here. All the patients underwent laparotomy for their management. The age range of the patient was 14 to 70 years and most commonly involved age group was 21 to 30 years. Male to female ratio was 15.6:1. The incidence of penetrating injury predominated (64%) over non-penetrating injury and majority had stab injuries. Road traffic accident predominated in blunt injury. Small gut injury outnumbered all other injuries in both groups. Abdominal pain was the most frequent symptom. Most of the patient arrived in the hospital within 24 hours. Considering clinical presentations and results of investigations, decision for laparotomy was taken with prior resuscitation. doi: 10.3329/taj.v17i2.3452 TAJ 2004; 17(2): 84-88